2020
DOI: 10.31436/iiumlj.v28i1.498
|View full text |Cite
|
Sign up to set email alerts
|

The Concept and Application of Hibah as a Financial Instrument From the Malaysian Legal Perspective: An Analysis

Abstract: The principle of hibah (gift) is a popular subject in the Islamic law of administration, relating to wealth management. Hibah is a solution to deliver wealth to non-heirs apart from the wasiyyah (bequest) or faraid (succession) systems. However, in the broader context of wealth management in Malaysia, hibah has also been used as a financial instrument in the Islamic financial institutions’ products and services. Based on that, the legality and enforcement of hibah with regards to the related applicable laws in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The differences between the instruments of hibah, faraid and wasiyyah have been summarized by Kamarudin and Nor Muhamad (2018), as shown in Table 1 below: Cases involving hibah-related matters are under the Syariah Court jurisdiction, as stipulated in the Islamic Religious Administration Enactment and Syariah Court Enactment and most of the cases are on the validity of hibah and its jurisprudence (Muhamad et al, 2019). Hasan and Mohamad Zaizi (2020) observed that the classical hibah was merely a way of distributing assets among family members, made in accordance with the Muslim law of…”
Section: Jiabr 133mentioning
confidence: 99%
“…The differences between the instruments of hibah, faraid and wasiyyah have been summarized by Kamarudin and Nor Muhamad (2018), as shown in Table 1 below: Cases involving hibah-related matters are under the Syariah Court jurisdiction, as stipulated in the Islamic Religious Administration Enactment and Syariah Court Enactment and most of the cases are on the validity of hibah and its jurisprudence (Muhamad et al, 2019). Hasan and Mohamad Zaizi (2020) observed that the classical hibah was merely a way of distributing assets among family members, made in accordance with the Muslim law of…”
Section: Jiabr 133mentioning
confidence: 99%
“…Hibah Amanah became popular in the financial industry after it was introduced by Amanah Saham Nasional Berhad (ASNB) in the year 2013 (Noordin et al, 2016). A trust hibah contract is also known as a commercial hibah (Hassan & Zaizi, 2020) since it is an instrument commercialized by the financial industry in Malaysia, especially in the planning and property management section (Azhar, 2014;Azhar et al, 2014). Even now, it is found that there are Islamic banking institutions that collaborate with trust companies to offer trust grants, namely Bank Islam Malaysia Berhad with Amanah Raya Berhad (Islamic Bank, Amanah Raya Grant Document) and Bank Muamalat Malaysia Berhad with As-Salihin Trustee Berhad (Muamalat Bank, Pre-Hibah or Grant Document Declaration).…”
Section: Concept Of Hibah Amanahmentioning
confidence: 99%
“…From the perspective of Islamic law, there are several terms related to the gift of property, one of which is hibah. Hibah refers to an agreement whereby a person transfers ownership of his or her assets to another person during his or her lifetime without compensation (Hassan & Mohamad Zaizi, 2020). Thus, linguistically, hibah means gift or grant.…”
Section: Introductionmentioning
confidence: 99%